How to Promote Innovative Work Behavior among Academics - Ibus, Salbeha; Wahab, Eta; Ismail, Fadillah (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge sharing has been proven to contribute potential benefits to organizations. Nevertheless, studies on the impact of knowledge sharing on innovative work behavior were inadequately explored. This study attempts to identify the influence of knowledge sharing on innovative work behavior and the mediator role of self-efficacy. Three hundred fifty samples were collected from the academics and analyzed through correlation and structured equation modeling techniques. The findings showed that knowledge sharing was significantly affected by innovative work behavior (β = 0.34, p < .000) with self-efficacy. Whereas Knowledge Sharing (β = 0.55, p = .000) has a significant relationship with Self-Efficacy. While self-efficacy showed a significant relationship (β= .049, p=.000) towards innovative work behavior. It is also indicated for the same situation where it was explaining 49.2% of the variance for innovative work behavior. The model achieved the goodness of fit indices with values of Chisquare/df=1.927, GFI=0.924, CFI=0.967, TLI=0.959, RFI=0.934, IFI=0.919, and RMSEA=0.054. Self-efficacy was mediated on knowledge sharing with innovative work behavior. Results could provide higher education institutions an in-depth understanding of the importance of knowledge sharing and self-efficacy in stimulating innovative work behavior among the academics, which is valuable to extend the development of related works of literature.